Предмет: Алгебра,
автор: timerlanred
1 - (ab+6a^2b^2-4b^2)/(-2b)
2 - (-a^2b^3+3a^6b^2)/(4a^4b^2)
Ответы
Автор ответа:
0
- B * ( - A - 6A^2B + 4B ) / ( - 2B ) = ( - A - 6A^2B + 4B) : 2 =
= - 0.5A - 3A^2B + 2B
===============================================
- A^2B^2 * ( - B + 3A^4 ) / 4A^2 B^2 ) = ( B - 3A^4) : 4 =
= 0.25B - 0.75A^4
===============================================
= - 0.5A - 3A^2B + 2B
===============================================
- A^2B^2 * ( - B + 3A^4 ) / 4A^2 B^2 ) = ( B - 3A^4) : 4 =
= 0.25B - 0.75A^4
===============================================
Похожие вопросы